FINANCIAL DISTRESS SEBAGAI PEMODERASI PENGARUH OPINI AUDIT DAN PERTUMBUHAN PERUSAHAAN PADA AUDITOR SWITCHING - Tisna, Ni Wayan Wulan; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi, 2017)
Auditor who has a long relationship with the client is believed to be a consequence of high dependence that can create strong loyalty relationship and ultimately affect the mental attitude as well as their opinion. This type of research use associative method. The independent variable in this study is the audit opinion, and the growth of the company, while the variables of financial distress as a moderating variable, and the variable switching auditors as independent variables. The total sample uses 150 data with purposive sampling method. Analysis data using logistic regression analysis. The results showed that the audit opinion negatively affect the auditor switching. Growth company positive effect on the auditor switching. Financial distress weaken the influence of the audit opinion on the auditor switching.  Financial distress weaken the influence of the company's growth in the auditor switching . Keywords : financial distress, audit opinion, growth of the company, auditor switching
Keywords: financial distress, audit opinion, growth of the company, auditor switching